The gap between overweight and obesity status in children - (STROBE-compliant article) - Mărginean, Cristina Oana (Medicine (Baltimore), 2021)
Overweight might represent only the early stage of obesity or it might act as a trigger of self-awareness turning into an ideal chance for preventing further obesity development. The aim of this study was to assess the differences between overweight and obese children in terms of anthropometric, low-grade systemic inflammation, liver impairment and atherosclerotic risk. We performed a study on 132 children aged between 5 and 18 years, divided according to the BMI into 2 groups: group 1 to 76 obese children, and group 2 to 56 overweight children, assessing anthropometric, laboratory and elastography parameters. We obtained significantly higher values of anthropometric parameters in obese children versus overweight ones. We found higher levels of leukocytes, lymphocytes, AST, ALT, and E median (P = .0345, P = .0103, P < .0001, P = .0008 and P < .0001) in the obese group as compared to the overweight one. BMI was positively correlated with neutrophils, NLR, ESR, glycemia, anthropometric parameters, and E median (P = .0007/<.0001/.0018/.0044/<.0001/<.0001/<.0001/<.0001/<.0001/.0204); and negatively with lymphocytes and HDL-cholesterol (r = −0.2747/−0.2181, P = .0116/.0120). Our study underlined significant differences between overweight and obese children in terms of inflammatory status and liver impairment suggesting that the risk is directly related to the increase in BMI.